Serial Order in Planning the Production of Successive Morphemes of a Word - Roelofs, Ardi (Journal of memory and language, 1996)
Five implicit priming experiments examined whether the speech production system can plan noninitial morphemes of a word in advance of initial ones. On each trial, subjects had to produce one word out of a set of three words as quickly as possible. In a homogeneous condition, the responses shared part of their form, whereas in a heterogeneous condition they did not. The first experiment shows that the task is sensitive to morphological planning. In producing disyllabic simple and compound nouns, a larger facilitatory effect was obtained when a shared initial syllable constituted a morpheme than when it did not. The next three experiments suggest that successive morphemes are planned in serial order. In producing nominal compounds, no facilitation was obtained for noninitial morphemes. In producing prefixed verbs, facilitation was obtained for the prefix but not for the noninitial base. Sharing morphemes often implies semantic overlap. The fifth experiment shows that semantic similarity per se yields inhibition rather than facilitation. Computer simulations show that the WEAVER model of word-form encoding (Roelofs, 1992b, 1994, submitted-a) accounts for the findings.